Free text adversity statements as part of a contextualised admissions process: a qualitative analysis - Lysa E. Owen (BMC Medical Education, 2018)
Abstract Background Medical schools globally are encouraged to widen access and participation for students from less privileged backgrounds. Many strategies have been implemented to address this inequality, but much still needs to be done to ensure fair access for all. In the literature, adverse circumstances include financial issues, poor educational experience and lack of professional-status parents. In order to take account of adverse circumstances faced by applicants, The University of Dundee School of Medicine offers applicants the opportunity to report circumstances which may have resulted in disadvantage. Applicants do this by completing a free text statement, known as an ‘adversity statement’, in addition to the other application information. This study analysed adversity statements submitted by applicants during two admissions cycles. Analysis of content and theme was done to identify the information applicants wished to be taken into consideration, and what range of adverse circumstances individuals reported. Methods This study used a qualitative approach with thematic analysis to categorise the adversity statements. The data was initially analysed to create a coding framework which was then applied to the whole data set. Each coded segment was then analysed for heterogeneity and homogeneity, segments merged into generated themes, or to create sub-themes. Results The data set comprised a total of 384 adversity statements. These showed a wide range of detail involving family, personal health, education and living circumstances. Some circumstances, such as geographical location, have been identified and explored in previous research, while others, such as long term health conditions, have had less attention in the literature. The degree of impact, the length of statement and degree of detail, demonstrated wide variation between submissions. Conclusions This study adds to the debate on best practice in contextual admissions and raises awareness of the range of circumstances and impact applicants wish to be considered. The themes which emerged from the data included family, school, personal health, and geographical location issues. Descriptions of the degree of impact that an adverse circumstance had on educational or other attainment was found to vary substantially from statements indicating minor, impact through to circumstances stated as causing major impact.